Criminal Law Policy Against Illegal Logging as an Effort to Protect National Forest Areas (Study on Solok Protection Forest Management Unit) - Otong Rosadi; Dedi Afrizal (Master of Law Program, Ekasakti University, 2023)
The criminal act of illegal logging in detail has been regulated in Law Number 41 of 1999 concerning Forestry although the law does not mention the term illegal logging in limitation. In an effort to improve ecological functions and restore natural resource reserves, the West Sumatra Provincial government has made policies to reduce the rate of forest destruction (per year) through efforts to reduce critical land area and maintain forest sustainability, including by protecting forests from illegal logging and forest fires which are the cause of forest destruction. The problems discussed in this study are (1) what is the criminal law policy carried out in the context of preventing and enforcing the law against illegal logging? (2) What efforts can be made to enforce the law against illegal logging? This research is a legal research with analytical descriptive specifications. The approach used is the Normative Juridical approach as the main approach supported by the Empirical Juridical approach. The data used are secondary data and primary data collected through literature studies and interviews. The data obtained are analyzed qualitatively and presented in an analytical descriptive form. Based on the results of the discussion and analysis, it can be concluded that First, the Criminal Law Policy Carried Out in the Framework of Prevention and Enforcement of Illegal Logging Crime is illustrated in the Legal Policy on illegal logging based on Law Number 41 of 1999 concerning Forestry which explains crimes in the forestry sector formulated as stated in Article 50 and Article 78, However, the so-called forestry crime is not formulated firmly, giving rise to multiple interpretations in some circles. Second, Law enforcement efforts against Illegal Logging crimes that can be carried out are: Harmonizing regional regulations with Law Number 41 of 1999 concerning Forestry, Providing severe sanctions against perpetrators of illegal logging crimes, Improving coordination between fellow law enforcement officials and with other related agencies, Eradicating corruption through the application of Law Number 31 of 1999 as amended by Law Number 20 of 2001 concerning the Eradication of Criminal Acts of Corruption, Entrapping perpetrators of illegal logging crimes integrally (comprehensively), and Increasing the facilities, infrastructure, and operational budget for handling cases of illegal logging.